The satisfaction of the population of the region the quality of the ambulance service - Kolesnikov, A.V.; Breusov, A.V.; Shichanin, V.V.; Breusov, R.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Medit͡s︡ina, 2017)
The state of health of the population substantially depends on quality and availability of a medical care. At the same time one of key aspects of the concept “quality of a medical care” is satisfaction of the patient from contact to personnel of the medical organization, especially with experts of emergency medical service. Authors set the object - to analyse the level of satisfaction of the population with the provided emergency medical service. During the research on specially developed questionnaire containing 6 blocks of questions, the continuous method interviewed 835 people. It is established that vast majority of respondents - 61,4% caused crew of emergency medical service not less than 1 time a year, 16,3% - at least 1 time in 2 months and in 22,3% of cases addressed for the first time. On time of arrival of crew for a call in 69,2% of cases questioned declared that the crew of emergency medical service comes to them within 20 minutes, in 17,1% of cases - in an interval from 20 to 40 minutes, in 8,3% - from 40 to 60 minutes, longer time of expectation was noted by 5,4% of respondents. The positive effect from assistance within the first 30 minutes occurred at 65,2% of patients, in later terms - at 31,3%, in 3,5% of cases patients didn't note at themselves effect of the medical events held by crew of SMP. In general, patients estimated quality of rendering emergency medical service in the region at 4,12 points. The received results will allow to develop a complex of the actions referred on optimization of rendering emergency medical service in the conditions of the large industrial region.